An efficient mechanochemical synthesis of amides and dipeptides using 2, 4, 6-trichloro-1, 3, 5-triazine and PPh31. Issue 65 (16th July 2015) - Duangkamol, Chuthamat; Jaita, Subin; Wangngae, Sirilak; Phakhodee, Wong; Pattarawarapan, Mookda
<x xml:space="preserve">Abstract</x> A mechanochemical method for amidation of carboxylic acids and urethane-protected (Fmoc, Cbz, Boc) α-amino acids has been developed as a facile, efficient, and eco-friendly route toward amides and dipeptides.